Hearing aid affordability in the United States. (3rd April 2023) - Jilla, Anna Marie; Johnson, Carole E.; Huntington-Klein, Nick
Abstract: Purpose: Substantial out-of-pocket costs for hearing aids constitute a barrier to hearing health care accessibility for older adults among whom prevalence of hearing loss is high. This study is the first to estimate the proportion of Americans with functional hearing loss for which out-of-pocket expenditures for hearing aids would be unaffordable at current average costs and determine how affordability varies by sociodemographic factors. Materials and methods: We utilized data from the 2016 American Community Survey to determine the proportion of adults with functional hearing loss for whom hearing aids would constitute ≥3% of annual income or have post-purchase income below a poverty standard. Chi-square tests were used to identify differences in affordability outcomes by sociodemographic characteristics. Results: Results indicated that an average bundled cost of $2500 would constitute a catastrophic expense for 77% of Americans with functional hearing loss ( N  = 7, 872, 292) and would add an additional 4% of the population into poverty for the year ( N  = 423, 548). Affordability outcomes varied significantly by age, race, sex, educational attainment and geographic location. Conclusions: Hearing aids were unaffordable for three-fourths of Americans with functional hearing loss, and their purchase would result in impoverishment for hundreds of thousands of individuals. Reductions in out-of-pocket hearing aid costs to $500 or $1000 would alleviate affordability issues for many Americans with hearing loss. Future federal and state policy should address poor rates of insurance coverage for hearing care, specifically among Medicare and Medicaid, to reduce out-of-pocket costs for hearing care particularly for older adults. Implications for rehabilitation: An average out-of-pocket hearing care cost of $2500 was unaffordable for over three quarters of Americans with functional hearing loss. Hearing care affordability varied significantly by demographic characteristics such as age, sex, gender, educational attainment and geographic region. Affordability constitutes a significant barrier to hearing care accessibility in the United States, where most costs of hearing aids and rehabilitation are statutorily excluded from insurance coverage, including the largest insurer of Americans, Medicare.